Hydric behaviour and gas exchange in different grapevine varieties (Vitis vinifera L.) from the Maule Valley (Chile) - Gutiérrez-Gamboa, G.; Pérez-Donoso, A.G.; Pou-Mir, A.; Acevedo-Opazo, C.; Valdés-Gómez, H. (South African Journal of Enology and Viticulture, 2019)
In the near future, stomatal behaviour will be crucial to counteract conditions arising from climate change. Grapevine varieties are classified as either isohydric or anisohydric, depending on the sensitivity of stomata to water deficit and on their water potential homeostasis. However, the great variability observed in different studies indicates that a continuum exists in the range of stomatal sensitivity to water stress. Thus, more knowledge about the hydric behaviour and the gas exchange of isohydric and anisohydric grapevine varieties under different water conditions could lead to the development of irrigation strategies oriented at improving water-use efficiency, yield and berry composition. In this study, research was conducted in order to characterise the stomatal regulation of four different Vitis vinifera L. varieties, namely Pinot noir, Sauvignon blanc, Chardonnay and Merlot, according to soil water status. Measurements of leaf gas exchange, together with measurements of stem water potential (Ψs) and leaf water potential (Ψl), were taken during two seasons. Under conditions of water stress, Chardonnay and Merlot reached a minimum Ψs of -1.67 and -1.68 MPa respectively, and higher levels of water-use efficiency (AN/gs), of 62.3 and 69.7 μmol CO2/mol H2O respectively. In Sauvignon blanc and Pinot noir, the minimum Ψs was -1.26 and -1.40 MPa respectively, with lower levels of AN/gs (53.1 and 50.5 μmol CO2/mol H2O, respectively). Under conditions of water stress (Ψl < -0.9 MPa and Ψs < -0.6 MPa), all varieties had a significantly increased AN/gs1, despite a significant reduction in gas exchange. Therefore, the hydric behaviour and gas exchange observed in this study suggest that Chardonnay and Merlot could be characterised as anisohydric varieties, as they present less sensitive stomatal control, while Pinot noir can be classified as a near-anisohydric variety and Sauvignon blanc as an isohydric variety. New investigations should consider other characteristics of the varieties to classify them better.